Formula (Fuaaila) in the Qur'an Al-Kareem between probabilistic interpretable and rhetoric miraculous - Assist. Prof. Dr. Jenan Nadem Hameed; Instructor Nahida Ghazi Alwan Al-Timimi (الأستاذ, 2017)
The research started towards the establishment and construction to replace alongside their probabilistic interpretation hyperbolic and guidance may be intentional guidance. Based on linguistic miracle, which is to preserve the building verbal as it is in the Qur'an Al-Kareem without saying that adapter from another building and maintaining the unity of the installation, which includes a word without saying: It is fitting word to delete it or increase where else. It is then no justification for this quantum of multiple direct indication of the words of the Qur'an al-Kareem, which is the one book revealed the God is one and came down with one angel on the heart of the Prophet and one his words one uniform each leading one meaning indicating not a multiple suspicious interpretive faces. It is where sneaks it likely direction The permissible? Search has chosen to apply the idea of ​​nine major examples of the Qur'an came to build Fuaaila, colorful sayings linguists and interpreters in touch significance both at the level of a single word or general construction. Those examples are: (rest and tranquility) and the two sides interpretation and (and the rest hostage) and two three aspects of interpretive and (pure and insight) and the two had four faces and (way) and the five aspects. And Praise be to Allah, the God of the Worlds.